Procedural justice, neighbourhood context, and domestic violence reporting intention among subgroups of immigrants - Yuan, Yue (Policing and society, 2022)
Although research shows immigrants are less likely to report crimes to the police than native-born individuals, few studies have examined domestic violence reporting behaviours among immigrant subgroups. Empirical studies have examined the role of procedural justice and neighbourhood factors on citizens’ satisfaction and willingness to cooperate with the police. However, these studies have often ignored immigrants’ willingness to report domestic violence in their neighbourhoods. To address the research gap in the crime reporting literature, this study uses a representative sample from a major US city with high concentrations of immigrants to examine whether there are differences in reporting domestic violence across various subgroups taking into account procedural justice and neighbourhood characteristics. We found that differences between subgroups of immigrants are reduced when procedural justice is included in the multilevel models. The study highlights the importance of procedural justice in understanding immigrants’ willingness to report domestic violence to the police.